Regional Location of Commercial and Household Service Complexes in Uzbekistan Regions Taking into Account Natural-Climatic Conditions (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
It consists in the development of recommendations and proposals for architectural and planning organization in the formation of commercial and consumer service complexes in the regions of Uzbekistan. One of the urgent problems of modern world urban planning is the process of development and formation of agglomerations. The greatest influence on these processes in recent years has been the growth of the urban population, its concentration in economically developed large cities, the strengthening of ties between individual cities and villages (both transport and social, household and labor ties). In the following years, a significant increase in the development process in the socio-economic sphere of our country was noticeable. As the cultural level and material well-being of the population of the republic grow, so does its activity, purchasing power, and demand for agglomeration-level institutions focused on entertainment and public services. All this is considered expedient to create objective conditions for the accelerated development of cultural, residential, shopping centers focused on serving public interests.